Peran Manajemen Logistik Bahan Baku dalam Mendukung Kelancaran Proses Produksi di PT International Packaging Manufacturing - Muhammad Efendy; Burhan Stafrezar (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study describes the role of raw material logistics management in supporting the continuity of production activities at PT International Packaging Manufacturing. The study was conducted through an internship in the Raw Material Logistics Division from April to July 2026 using a qualitative descriptive approach. Data were obtained through direct observation, interviews with field supervisors and logistics staff, and documentation of inventory-related activities. The observed activities included checking the quantity and condition of incoming materials, recording receipts and issues, arranging materials according to storage locations, monitoring inventory levels, conducting stock opname, and distributing materials to the production department. The results show that structured logistics management helps maintain material availability, improve inventory data accuracy, reduce the risk of shortages and excess stock, and support timely production. The integration of physical inspection, systematic recording, periodic reconciliation, and coordination between logistics and production is essential for preventing operational disruptions. The internship also demonstrates that information systems, clear work procedures, employee discipline, and effective communication strengthen inventory control. In addition to providing insight into warehouse operations, the internship improved the student’s communication, teamwork, accuracy, discipline, adaptability, and responsibility. These findings emphasize that reliable raw material logistics is a component of efficient manufacturing operations.